A Study of Environmental Awareness among Primary School Students in Some Schools in the Hashemite Kingdom of Jordan and the Sultanate of Oman for the Academic Year (2019/2020): A Comparative Study - Awad, Nasri; Hamdani, Mariam; Samha, Mousa (Dirasat: Educational Sciences, 2022)
Aims: The current study aims to identify the level of environmental awareness among primary school students in the schools of the Hashemite Kingdom of Jordan and the Sultanate of Oman for the academic year 2019/2020. Because of the small size of the study population, the study sample was selected by means of a comprehensive inventory of the study population. The study tool (a questionnaire) was distributed to (86) male and female students in Jordan, and (60) male and female students in the Sultanate of Oman. Methods: This study is based on the use of a descriptive comparative method. This method was used to suit the purposes of the study. A study of environmental awareness among primary school students was built in the form of a scale to collect study data. Results: The results of the study showed that environmental awareness among eleventh grade students in the Hashemite Kingdom of Jordan and the Sultanate of Oman came at an average level. Conclusions: The study recommends raising the level of medical warnings about smoking and its relationship to cancer diseases, and to introduce the role of civil society institutions to raise the level of environmental awareness.